Expression of Nestin associates with BRCA1 mutations, a basal-like phenotype and aggressive breast cancer - Kristi Krüger (Nature Portfolio, 2017)
Abstract We here examined whether Nestin, by protein and mRNA levels, could be a predictor of BRCA1 related breast cancer, a basal-like phenotype, and aggressive tumours. Immunohistochemical staining of Nestin was done in independent breast cancer hospital cohorts (Series I-V, total 1257 cases). Also, TCGA proteomic data (n = 103), mRNA microarray data from TCGA (n = 520), METABRIC (n = 1992), and 6 open access breast cancer datasets (n = 1908) were analysed. Patients with Nestin protein expression in tumour cells more often had BRCA1 germline mutations (OR 8.7, p < 0.0005, Series III), especially among younger patients (<40 years at diagnosis) (OR 16.5, p = 0.003). Nestin protein positivity, observed in 9–28% of our hospital cases (Series I-IV), was independently associated with reduced breast cancer specific survival (HR = 2.0, p = 0.035) and was consistently related to basal-like differentiation (by Cytokeratin 5, OR 8.7–13.8, p < 0.0005; P-cadherin OR 7.0–8.9, p < 0.0005; EGFR staining, OR 3.7–8.2, p ≤ 0.05). Nestin mRNA correlated significantly with Nestin protein expression (ρ = 0.6, p < 0.0005), and high levels were seen in the basal-like intrinsic subtype. Gene expression signalling pathways linked to high Nestin were explored, and revealed associations with stem-like tumour features. In summary, Nestin was strongly associated with germline BRCA1 related breast cancer, a basal-like phenotype, reduced survival, and stemness characteristics.